2021
DOI: 10.1016/j.jdermsci.2021.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Dermatology Life Quality Index at initiation or switching of biologics in real-life Japanese patients with plaque psoriasis: Results from the ProLOGUE study

Abstract: Background: Plaque psoriasis significantly affects patients' health-related quality of life. To aid treatment decisions, not only objective assessment by physicians but also subjective assessment by patients is important. Objective: To assess the significance of Dermatology Life Quality Index (DLQI) evaluation at the time of biologics introduction in clinical practice in Japanese patients with plaque psoriasis. Methods: This was a single-arm, open-label, multicenter study. At baseline, Psoriasis Area and Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
56
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 48 publications
5
56
0
2
Order By: Relevance
“…Psoriasis is a recurrent, persistent inflammatory skin disorder characterized by rough, reddish plaques on frequently chafed body parts, such as the extensor sites of the extremities [ 1 , 2 ]. Individuals with this condition suffer from subjective symptoms, such as itching and pain, but also from skin lesions, especially on exposed areas, such as the scalp, face, hands, and nails, which can have a prominent impact on the patients’ quality of life [ 3 , 4 , 5 , 6 ]. In fact, it has been suggested that the manifestation of psoriasis-related symptoms can trigger stigmatization, leading to social discrimination and alienation [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is a recurrent, persistent inflammatory skin disorder characterized by rough, reddish plaques on frequently chafed body parts, such as the extensor sites of the extremities [ 1 , 2 ]. Individuals with this condition suffer from subjective symptoms, such as itching and pain, but also from skin lesions, especially on exposed areas, such as the scalp, face, hands, and nails, which can have a prominent impact on the patients’ quality of life [ 3 , 4 , 5 , 6 ]. In fact, it has been suggested that the manifestation of psoriasis-related symptoms can trigger stigmatization, leading to social discrimination and alienation [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The burden of having both itching and skin pain in real-life patients with psoriasis has not been fully elucidated. To assess the effects of co-occurrence of itching and skin pain in real-life patients with psoriasis using multiple patient-reported outcome (PRO) instruments, we analyzed the baseline patient data of the ProLOGUE study, which assessed the effectiveness of brodalumab, a human anti-interleukin-17 receptor monoclonal antibody, in Japanese patients with plaque psoriasis (Japan Registry of Clinical Trials identifier: jRCTs031180037) [5]. This single-arm, open-label, multicenter, prospective study was conducted at 15 facilities across Japan from October 2017 to March 2020.…”
mentioning
confidence: 99%
“…This single-arm, open-label, multicenter, prospective study was conducted at 15 facilities across Japan from October 2017 to March 2020. Patients (aged ≥ 18 years) who had plaque psoriasis without peripheral arthritis symptoms and who could self-administer brodalumab were included [5]. The level of itching and skin pain (during the previous 24 h) were assessed using the Itch Numeric Rating Scale (NRS) [6] and Skin Pain NRS [7] scores, respectively (0 [no itch/pain] to 10 [worst imaginable itch/pain]).…”
mentioning
confidence: 99%
See 2 more Smart Citations